English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can someone help me factor this and show work?

4-4x^2-4y^2+8xy

2007-02-15 09:46:20 · 4 answers · asked by Jeff 2 in Education & Reference Homework Help

4 answers

4 - 4x^2 - 4y^2 +8xy

4 +(- 4x^2 + 8xy - 4y^2) = (-2x+2y)(2x-2y) + 4

(-2x+2y)(2x-2y)+4 --- factored back is, (-2x*2x)+(-2x*-2y)+(2y*-2x)+(2y*-2y) = -4x^2 +4xy +4xy -4y^2 = -4x^2 +8xy -4y^2 now u can add in your 4 u had to start

if u want to go farther with that you can do:

4( 1 - x^2 -y^2 +2xy) ===> 4(1 + ((-x+y)(x-y)))

2007-02-15 10:08:18 · answer #1 · answered by Anonymous · 0 0

hello ...

4 - 4 x ^2 - 4 y^2 + 8xy
= 4(1 - 1 (x ^2 2+ y^2 - 2xy ) ( (a ^2 + b^2 - 2ab = (a+b)(a+b))
= 4 ( 1^2 - ( x - 2)^2 ) ( use a^2 - b^2 = ( a - b)(a + b)
= 4 ( 1- x + 2 )( 1 +x - 2)

hope this will help you ..:)

2007-02-15 10:08:27 · answer #2 · answered by RAKESHtutor 3 · 0 0

4 - 4x^2 -4y^2 +8xy
-4(x^2 -2xy + y^2)
-4(x - y)(x - y) or -4(x-y)^2

done

2007-02-15 09:51:01 · answer #3 · answered by Grover 3 · 1 0

I don't understand your equation. What does - mean?

2007-02-15 09:50:45 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers